Implementation of IoT-Based Aquaponics Technology to Enhance Food Security and Economic Independence at Berkah Box Mosque: Penerapan Teknologi Akuaponik Berbasis IoT untuk Meningkatkan Ketahanan Pangan dan Kemandirian Ekonomi di Masjid Berkah Box - Alif, Muhammad Ikhsan; Prabowo, Agung; Amir, Supratiwi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to support local food security at Masjid Berkah Box through the implementation of Internet of Things (IoT)-based aquaponic technology. The activities began with location observation and identification of available resources. Next, the team designed an aquaponic system that integrates temperature, humidity, and water flow monitoring using sensors and the Arduino platform. The system implementation includes the installation of water pumps, filters, and sensors, as well as initial trials to ensure the stability of environmental parameters for the growth of fish and plants. Training and education were provided to the community on how to maintain the IoT-based aquaponic system, with the goal of enhancing knowledge and skills in modern agriculture. The results of the service showed a significant increase in participants' understanding and skills regarding aquaponic technology, as evidenced by pre-and post-training surveys. A total of 80.7% of participants felt they had a better understanding of the aquaponic concept after the training, and 66.19% felt more confident to engage in aquaponic activities. Periodic evaluations were conducted to monitor plant growth and fish health, which showed that the system operates efficiently and is capable of providing a sustainable food source. The implications of this activity include the utilization of previously unproductive land into valuable resources and improving the quality of life of the community by providing healthy food and additional income from the sale of aquaponic products. This program also contributes to reducing air pollution and mosquito populations in the vicinity of the mosque